Data Gathering Optimization in Wireless Sensor Networks Using Unmanned Aerial Vehicles - Vladuta, Valentin-Alexandru; Matei, Ioana; Bica, Ion (International Conference on Control Systems and Computer Science (Online), 2019)
Data gathering from wireless sensors using unmanned aerial vehicles has been a subject of interest in the recent years. Scientific literature shows that this method has not reached its peak and results are promising, as can be seen from Section 2. Sensors were included in different areas with the sole purpose of optimizing results (traffic management, crop field surveillance and many more). Beside obvious advantages that they bring, they offer also limitations in terms of hardware/software capabilities. For this reason, this paper addresses the need of reducing the transmission time and energy consumption due to the limited capacities of wireless sensors. The most important part of the proposed optimization relies in the dynamic construction of the trajectory that an unmanned aerial vehicle uses for gathering data from wireless sensors. The trajectory will be built based on a file that contains the positions of all sensors in the field. The file would be created in a previous step, when the unmanned aerial vehicle would fly on a predefined pattern and discover sensors on the ground. Based on the locations of the sensors, grouping and optimizations are done to obtain the best trajectory for the given location of sensors. Simulations were made with Network Simulator 2 and results show that the proposed objectives have been reached.